Small Business E-Commerce Management - "Chaston, Ian" ("Houndmills, New York :")
Includes an index
Keywords: ELECTRONIC COMMERCE - MANAGEMENT;BUSINESS ENTERPRISE - COMPUTER NETWORKS;SMALL BUSINESS - COMPUTER NETWORKS